(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2017)
Biosurfactants are extracellular macromolecules produced by bacteria, yeast, and fungi when grown on different carbon sources. It has the ability to reduce the surface tension of a liquid, interfacial tensions between two liquids and between a liquid and a solid. This study was conducted to isolate potential biosurfactant producers from oil-contaminated soil and water. Soil and water samples were obtained from the food court area in front of Universiti Malaysia Kelantan, Jeli Campus. Isolation of biosurfactant producing bacteria was carried out on minimal salt medium (MSM) supplemented with palm oil as the sole carbon source. Five potential biosurfactant producers; WS2, WS4, WS5, SS2 and SS5 were successfully isolated and identified by 16S rRNA analysis. Isolate WS4, SS2 and SS5 showed the highest similarity to Klebsiella sp and the other two isolates, WS2 and SS5 showed the highest similarity to Pseudomonas sp. and Nanobacterium sp. respectively. While Klebsiella sp. and Pseudomonas sp. were reported as prevalent biosurfactant producer, no report is available on the production of biosurfactants by Nanobacterium sp. All isolates showed variation in biosurfactant characterization assays which are emulsification test, drop collapse test, oil spreading test, blood haemolysis and blue agar plate assay.